Determinants of Continuous Intention to Use Mobile Payment in Nigeria - Ejike Miracle Okechukwu; Nwosu Kanayo Chike (Trescode Green Organization, 2025)
The upsurge in m-payment usage despite multiple challenges is unfathomable. The research aims to determine the factors influencing the continuous intention to use m-payment in Southeast, Nigeria. The survey was anchored on the diffusion of innovation, technology acceptance model, and unified theory of acceptance and use of technology. A structured questionnaire was used for data collection while standard multiple regression was used for data analysis. The study found a positive statistical influence of perceived advantage, usefulness, safety, and cost on continuous intention to use mobile payment in Southeast, Nigeria. It was recommended that financial institutions should often upgrade the m-payment system to meet the requirements of users; be more aggressive in promoting the use of m-payment in Nigeria; use safety attributes to position the payment system in the minds of users; and position m-payment as a tool for cost-effective payments.